Wildlife conservation legislations in Malaysia: Sustainable Livelihood · Prudent Utilization · Management of Natural Resources 13 Wildlife Conservation Legislations in Malaysia: Evolution and Future Needs - Jayasilan, Mohd. Azlan (Universiti Malaysia Sarawak (UNIMAS), 2014)
Malaysia is considered a leader among Southeast Asian countries with regard to conservation legislation and programs; it was among the first ASEAN country to develop national conservation legislation, sign CITES, and develop a national conservation strategy. Malaysia has a protected area system covering over 12% of its land area, and many target species occur in parks and reserves. As many species are being included in the endangered species list, there are also some causes of concern, including staff shortages, financial constraints, and inconsistencies within wildlife protection legislations between Peninsular Malaysia, Sabah and Sarawak. This paper looks into selected threats to wildlife in Sarawak and compare legislations relating to wildlife protections in Malaysia. Primary needs include a comprehensive review of these legislations and a nationalized strategy to ameliorate the shortcomings.